Penggunaan Media Kartu Bergambar Sebagai Upaya Meningkatkan Minat Baca Anak Usia Dini di Pos Paud Mutiara Bundaku Malang - Loesita Sari; Yulita Pujiharti; Naniek Kuscahyani (IKIP Budi Utomo Malang, 2017)
The purpose of this study is to determine the use of the media card image as an effort to increase students’s Interest in reading Pos Paud Mutiara Bundaku Malang. This study used a comparative approach with research and development and statistic analysis. The Subject involved the students of Pos Paud Mutiara Bundaku Malang which consisted of 13 students. The Sources of data were documents containing result of pretest and postest methods, interviews and obsevation. Based on the research analysis, it was found that the children’s interst in reading media picture card increased to be 7.68 better than before at the score of 69.23.